Strengthening Teacher Performance through Professionalism, Discipline, and Organizational Climate: Evidence from Islamic Primary Education - Hanifah Yunita; Tin Agustina Karnawati; Teguh Widodo (Journal of Educational Management Research, 2026)
This study aims to examine the effect of professionalism, work discipline, and organizational climate on teacher performance as a key component of educational service quality. Using a quantitative approach with an explanatory research design, the study involved a census of 34 teachers in an Islamic primary school, with data collected through Likert-scale questionnaires and analyzed using multiple linear regression with t-tests and F-tests at a 5% significance level. The findings indicate that professionalism and organizational climate have a positive and significant effect on teacher performance, while work discipline shows no significant partial effect. However, professionalism, discipline, and organizational climate simultaneously exert a significant influence on teacher performance. These results highlight the importance of strengthening teacher professionalism and creating a supportive organizational climate as strategic educational management efforts to improve teacher performance, while discipline enhancement should be aligned with workload management to ensure effective implementation